2009
DOI: 10.1186/1471-244x-9-9
|View full text |Cite
|
Sign up to set email alerts
|

The PsyCoLaus study: methodology and characteristics of the sample of a population-based survey on psychiatric disorders and their association with genetic and cardiovascular risk factors

Abstract: Background: The Psychiatric arm of the population-based CoLaus study (PsyCoLaus) is designed to: 1) establish the prevalence of threshold and subthreshold psychiatric syndromes in the 35 to 66 year-old population of the city of Lausanne (Switzerland); 2) test the validity of postulated definitions for subthreshold mood and anxiety syndromes; 3) determine the associations between psychiatric disorders, personality traits and cardiovascular diseases (CVD), 4) identify genetic variants that can modify the risk fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
222
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 195 publications
(223 citation statements)
references
References 76 publications
1
222
0
Order By: Relevance
“…Such an association with the BMI was not observed in the whole PsyCoLaus sample, but CRTC1 SNPs were associated with BMI in the Radiant study. BMI may less accurately capture adiposity than estimated fat mass using bioimpedance (Marques-Vidal et al, 2009;Prentice and Jebb, 2001). Using the whole CoLaus sample, previous work established that fat mass enables capture of 3 times more subjects with high cardiovascular risk than BMI(Marques-Vidal et al, 2009) and we also showed that this sample is better powered to detect an association of the rs6510997C>T SNP with fat mass than with BMI (Choong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an association with the BMI was not observed in the whole PsyCoLaus sample, but CRTC1 SNPs were associated with BMI in the Radiant study. BMI may less accurately capture adiposity than estimated fat mass using bioimpedance (Marques-Vidal et al, 2009;Prentice and Jebb, 2001). Using the whole CoLaus sample, previous work established that fat mass enables capture of 3 times more subjects with high cardiovascular risk than BMI(Marques-Vidal et al, 2009) and we also showed that this sample is better powered to detect an association of the rs6510997C>T SNP with fat mass than with BMI (Choong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a genome-wide association study was performed in all Caucasians (91% of the sample). All participants of CoLaus were asked to also participate in the psychiatric evaluations (PsyCoLaus (Preisig et al, 2009)), which included the semi-structured Diagnostic Interview for Genetic Studies (DIGS) (Nurnberger et al, 1994;Preisig et al, 1999). The assignment of the lifetime diagnosis of MDD and the subtyping into atypical and non-atypical MDD was performed according to DSM-IV criteria.…”
Section: Discovery Cohort: Colaus|psycolausmentioning
confidence: 99%
“…In addition to demographic features, the French version of the DIGS comprises information on a broad spectrum of DSM-IV Axis I disorders as well as on some Axis II criteria and suicide behavior (Preisig, et al, 2009). According to the DIGS participants were coded as having an AUD if they met criteria for either alcohol abuse or dependence according to the DSM-IV at any point of their lives.…”
Section: Methodsmentioning
confidence: 99%
“…The HypnoLaus Sleep Cohort study included participants of the population-based CoLaus/PsyCoLaus Cohort study described previously [9,10]. Briefly, the CoLaus/PsychoLaus study included a random sample of 6,734 participants (age range: 35-75 years) selected from the residents of Lausanne city (Switzerland) between 2003 and 2006.…”
Section: Participantsmentioning
confidence: 99%